O PSS e a coordenação de segurança na construção - Telmo Dias Pereira (Ensino, 2019)
Despite the sharp decline in activity seen in recent years, construction continues to be an industry with a huge number of accidents at work, particularly in terms of the number of serious and fatal accidents. This book presents an in-depth view of the problem of safety in construction, taking into account above all the transposition into national law of the "Shipyard Directive" through Decree-Law no. 273/2003 of October, 29. The main aspects of the implementation of safety in construction are detailed, including the elaboration of the Safety and Health Plan (SHP) as well as the performance of technicians who carry out the designated Safety Coordination (SC).